UPAYA MENINGKATKAN FOKUS BELAJAR SISWA KELAS I SD MELALUI MODEL CHALLENGE-BASED LEARNING - Norrifansyahh; Rahmadi; Fakhruddin; Sujarwoko; Fani Arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to enhance the learning concentration of first-grade students at SDN 2 Loktabat Selatan in Physical Education (PJOK) by employing the Challenge-Based Learning (CBL) approach. The research was prompted by diminished student engagement, manifesting in inattentiveness during instructor presentations, susceptibility to distractions, reduced participation in learning activities, and an inability to adhere to instructions proficiently. The employed research methodology was Classroom Action Research (CAR), executed in two cycles, encompassing the phases of planning, implementation, observation, and reflection. The data gathering methods comprised observation, documentation, and student learning assessment sheets. The Challenge-Based Learning paradigm was executed via challenge-based activities, games, collaborative group work, and straightforward problem-solving in PJOK education. The results indicated an enhancement in student concentration on learning.